An Automated Obstacle Detector and Path Finder Robotic Car - Mohammad Shamiur Rahman Al Nahian; Arnab Piush Biswas (Politeknik Negeri Padang, 2020)
This is to present you a simple and cost-efficient obstacle detecting mobile robot. Here a controlled rotating sonar sensor has been used to measure distance. With this robot the angular and distance values are being sampled with the system support and being simplified to get a correct way through the given algorithm. The system was implemented in C++ type Arduino coding Software. Inputting the data and processing it in Arduino; all were digitally maintained; the digital pins of Arduino were used. And the outputs were controlled by the Arduino which were pre-given. This simple, cost efficient and mostly accurate project can be used in farming as well as defense and security sector of any country.